EDUKASI HUKUM TENTANG LITERASI MEDIA TERKAIT HOAKS BENCANA DI SMK YADIKA 2 TANJUNG DUREN JAKARTA - Natalia Yeti Puspita; Jane Madeline (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Nowadays fake news or hoaxes are increasingly prevalent in people's lives, especially when a disaster occurs. In a disaster situation, various disaster-related information is immediately circulated in the community, but not all of the information is correct and can be accounted for. Hoax perpetrators aim to spread fear and sometimes even have criminal or political motives. Hoaxes are widely spread through social media. One form of resistance to hoaxes is to build community competence, especially young people, through media literacy related to disasters in dealing with information overload. With this legal education, young people can understand their rights and obligations in obtaining correct information about an ongoing disaster based on Article 26 and 27 of Law Number 24 of 2007 concerning Disaster Management. In addition, it also provides an understanding for young people that the spread of hoaxes during disasters violates Law Number 11 of 2008 concerning Information and Electronic Transactions. Legal education on media literacy related to disaster hoaxes was held for class XII students of SMK Yadika 2 in Tanjung Duren Jakarta. With this legal education, it is hoped that students of SMK Yadika 2 can participate and be involved in preventing hoaxes when the flood disaster hits Jakarta.